A geografia do café e o Novo Oeste Paulista - Anselmo Alfredo (Confins)
It discusses the unity between familiar labor in the new west paulista coffee plantation, the consecration of Catholic family and the exploration of the work. In this process, the geographical expedition in this unknown backcountry will have a significative role in the expansion of both the agricultural frontier and the National State in the passage to the XXIth century.